Alternative dispute resolution and mediation of complaints against police in Australia and New Zealand. (2nd January 2020) - Riley, Mary; Prenzler, Tim; McKillop, Nadine
ABSTRACT: This study assessed the role of alternative dispute resolution options in the complaints management systems of the eight policing jurisdictions in Australia and the single jurisdiction of New Zealand. The available literature shows that a large proportion of complainants would like to participate in mediation, and that both complainants and police who experience mediation report much higher rates of satisfaction than those experiencing traditional adversarial investigative and adjudicative processes. Experiences with informal dispute resolution or 'conciliation' options are more mixed, and they are susceptible to tokenism and misuse as a convenient administrative means of disposing of complaints. Despite this situation, the data obtained from police and oversight agency sources in this study showed that options were limited to informal resolution conducted by senior officers, with an ostensible focus on behavioral improvement but with no meaningful publicly available data on outcomes. The paper concludes by advocating for a best practice complaints management system that includes mediation within a consultative framework focused on behavioral improvement.